Bluetooth application programming with the Java APIs - Kumar, C. Bala.; Kline, Paul J.; Thompson, Timothy J. (Timothy Joseph), 1976-; Motorola Semiconductor Products Sector (San Francisco, CA : Morgan Kaufmann, 2004)
Adoption of Bluetooth wireless technology has made great strides in the last few years. One of the biggest steps forwardthe standardization of Java APIs for Bluetooth wireless technology (JABWT)is explained in detail in this book. The JABWT standard, defined by the JSR-82 specification, supports rapid development of Bluetooth applications that are portable, secure, and highly-usable. Wireless device manufacturers have responded to the JABWT specification by announcing mobile phones and other products that will run JABWT applications. Bluetooth Application Programming with the Java APIs explains in detail how to write Bluetooth applications using the Java APIs to exploit the power of both technologies. Written by the specification lead for JSR-82 and two other key participants in the definition of JABWT, this book provides the authoritative explanations and concrete examples you need to get started right away. About the Authors C Bala Kumar is a Distinguished Member of the Technical Staff at Motorola. He chaired the industry expert group that defined the Java APIs for Bluetooth wireless technology. He currently leads the systems software team for wireless platforms in Motorola's Semiconductor Products Sector. Paul J. Kline is a Distinguished Member of the Technical Staff at Motorola and the maintenance lead for the JABWT specification. He currently works on the System Software Architecture team in Motorola's Semiconductor Products Sector. Timothy J. Thompson is a Senior Software Engineer on the System Software Architecture team in Motorola's Semiconductor Products Sector. He was the OBEX architect on the JABWT specification team at Motorola. * Written by expertsthe authors led the industry team that defined the JABWT standard and the Motorola team that developed the first JABWT implementation * Covers JABWT in depth and goes beyond the specification to explain how to use the standard effectively * A helpful resource both to Java programmers interested in Bluetooth wireless technology and to business managers interested in its potential for creating new business opportunities * Digs deeply into the programming areas you must master to successfully design and build JABWT applications, including RFCOMM, OBEX, device discovery, service discovery, and L2CAP * Details the real-world issues involved in programming Bluetooth devices and implementing the JABWT specification * Organized into sections that explicitly address the different needs of programmers, business managers, and project managers.
Chapter 1 Introduction -- 1.1 Wireless Connectivity -- 1.2 What is Bluetooth Wireless Technology? -- 1.3 Overview of the Bluetooth Stack architecture -- 1.4 What is J2ME? -- 1.5 Why Java Technology for Bluetooth Devices? -- 1.6 Summary -- Chapter 2 An Overview of JABWT -- 2.1 Goals -- 2.2 API Characteristics and Hardware Requirements -- 2.3 Scope -- 2.4 Summary -- Chapter 3 High-Level Architecture -- 3.1 Architecture of JABWT -- 3.2 Bluetooth Control Center -- 3.3 Simple JABWT Application -- 3.4 Summary -- Chapter 4 RFCOMM -- 4.1 Overview -- 4.2 API capabilities -- 4.3 Programming with the API -- 4.4 Summary -- Chapter 5 OBEX -- 5.1 Overview -- 5.2 API Capabilities -- 5.3 Programming with the API -- 5.4 Summary -- Chapter 6 Device Discovery -- 6.1 Overview -- 6.2 API capabilities -- 6.3 Programming with the API -- 6.4 Summary -- Chapter 7 Service Discovery -- 7.1 Overview -- 7.2 API capabilities -- 7.3 Programming with the API -- 7.4 Summary -- Chapter 8 L2CAP -- 8.1 Overview -- 8.2 API Capabilities -- 8.3 Programming with the API -- 8.4 Summary -- Chapter 9 Example Applications -- 9.1 Overview -- 9.2 Tic-Tac-Toe MIDlet -- 9.3 OBEX Application Download -- 9.4 Summary -- Chapter 10 Implementing JABWT on a Device -- 10.1 Porting Process -- 10.2 Steps 1 and 2: Adding J2ME and Bluetooth support -- 10.3 Step 3: Implementing JABWT -- 10.4 Step 4: TCK Compliance -- Chapter 11 Closing Remarks -- Appendix A: Complete Code Examples -- Appendix B: javax.bluetooth.api -- Appendix C: java.obex.api -- References -- Index.
Includes bibliographical references (p. [491]-492) and index.
Keywords: Bluetooth technology; Java (Computer program language).; Application program interfaces (Computer software); Wireless communication systems; API; Electronic books